2006
DOI: 10.1002/jez.a.282
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines inhibit neuronal activity in the glossopharyngeal–vagal motor complex of the Japanese eel: significance for controlling swallowing water

Abstract: To clarify neuronal networks controlling swallowing water, inhibitory neurotransmitters were searched on the glossopharyngeal-vagal motor complex (GVC) of the medulla oblongata (MO), which is proposed as a motor nucleus controlling swallowing. Spontaneous firing (20-30 Hz) in the GVC was inhibited by adrenaline (AD), noradrenaline (NA) and dopamine (DA). The inhibitory effects of these catecholamines (CAs) were dose-dependent, and the effects of AD and NA were completely blocked by phenoxybenzamine or yohimbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Furthermore, it has been shown that the GVC neurons project directly to the striated muscles of the opercular membrane, pharynx, upper esophageal sphincter and esophageal body, all of which are implicated in swallowing (Mukuda and Ando, 2003b). It was also shown that the AP neurons project ventrally to the GVC (Ito et al, 2006). Although further experiments are required to identify precise neuronal networks that are involved in ANP-induced inhibition of drinking, it is possible that the AP acts as a center for integrating the information of dipsogenic and antidipsogenic hormones from the periphery and that it regulates the coordinated behaviour of swallowing through the vagus nerves in eels.…”
Section: Table·1 Brain Loci Stained By Trypan Blue and Npr-a Immunohmentioning
confidence: 99%
“…Furthermore, it has been shown that the GVC neurons project directly to the striated muscles of the opercular membrane, pharynx, upper esophageal sphincter and esophageal body, all of which are implicated in swallowing (Mukuda and Ando, 2003b). It was also shown that the AP neurons project ventrally to the GVC (Ito et al, 2006). Although further experiments are required to identify precise neuronal networks that are involved in ANP-induced inhibition of drinking, it is possible that the AP acts as a center for integrating the information of dipsogenic and antidipsogenic hormones from the periphery and that it regulates the coordinated behaviour of swallowing through the vagus nerves in eels.…”
Section: Table·1 Brain Loci Stained By Trypan Blue and Npr-a Immunohmentioning
confidence: 99%
“…The commissural nucleus of Cajal (NCC), homologous to the nucleus tractus solitarius of mammals, is innervated by viscerosensory neurons in the catfish, goldfish, and mullet (4,7,22), just as the nucleus tractus solitarius is innervated by the sensory neurons from baroreceptors and visceral organs in mammals. In eels, the NCC neurons project to the glossopharyngeal-vagal motor complex neurons that project to the upper esophageal sphincter muscle to control drinking (17,30). Therefore, it is possible that the reflexgenic afferent input from peripheral baroreceptors activated the NCC neurons directly and inhibited drinking without mediation of the AP.…”
Section: Discussionmentioning
confidence: 99%
“…This area is dominated by motoneurons that innervate the UES (Mukuda and Ando 2003a). These neurons typically fire spontaneously and show large amplitude spikes (>75 µV) (Ito et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…These motoneurons are cholinergic (Mukuda and Ando 2003a) and constrict the pharyngeal muscle and UES through acetylcholine (Kozaka and Ando 2003). Ito et al (2006) in the eel reported that motor neurons in GVC fire spontaneously at high frequency using the isolated brain specimens and the firing activity was inhibited by catecholamines.…”
Section: Introductionmentioning
confidence: 99%